Recommendations for iliosacral screw placement in dysmorphic sacrum based on modified in‐out‐in corridors. Issue 3 (5th January 2019) - Wendt, Henry; Gottschling, Heiko; Schröder, Manuel; Marintschev, Ivan; Hofmann, Gunther O.; Burgkart, Rainer; Gras, Florian
ABSTRACT: (1) Can iliosacral osseous corridor diameters in sacral dysmorphism be enlarged by in‐out‐in screw placement at the posterior iliosacral recessus? (2) Are lumbosacral transitional vertebra (LSTV) the anatomical cause for sacral dysmorphism? (3) Are there sex‐specific differences in sacral dysmorphism? 594 multislice CT scans were screened for sacral dysmorphism and 55 data‐sets selected. Each pelvis was segmented manually and cylindrical iliosacral corridors (on the level of S1 and S2 vertebra) were semi‐automatically determined. Corridor trajectories, −diameters and −lengths were measured. LSTV (Castellvi‐type IIIb and IV) were found in 3 of 55 pelves and these lumbosacral variations are therefore not the anatomical basis for sacral dysmorphism. The prevalence of transsacral osseous corridors with diameters of <7.5 mm in axial CT images correlates with qualitative and quantitative criteria of sacral dysmorphism. Enlarging the osseous corridor diameters by penetration of the posterior iliosacral recessus increase the safe corridor diameters (females versus males) by 26% versus 15% at the level of S1‐ and 50% versus 48% at the level of S2‐vertebra. Sex‐specific differences for both corridors (osseous and in‐out‐in) were only found for the osseous corridor diameters at the level of S1 vertebra, being smaller in females (females versus males: 13.3 ± 3.6 mm versus 15.5 ± 3.8 mm, p  = 0.04). Dysmorphic sacra can be reliably detected on standard axial CT slice images. Modified in‐out‐in corridors on the level of S1‐vertebra allow screw placement in all patients, but is still demanding compared to non‐dysmorphic sacra, due to the oblique corridor axis. Recommendations for intraoperative orientation for oblique screw placement are defined. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res